Economic policy uncertainty, global oil price, interest rate, and stock market returns - a cointegration and causality analysis - Yesuf, Abdurahman Jemal (My University, 2018)
Bir ülkenin ekonomik büyümesi borsalarının değişen dinamikleriyle yakından bağlantılıdır. Ekonomik faaliyetlerdeki temel rollerinden dolayı; borsaların işleyişi ve aşağı-yukarı hareketleri her zaman finansal kurumlar, şirketler, bireysel yatırımcılar ve hükümetler tarafından dikkatle takip edilmektedir. Hisse senedi piyasalarının getirileri makroekonomik göstergelerin sistematik etkisi ile belirlenmektedir. Bir ülkenin ekonomisini tanımlayan temel göstergeler, aynı zamanda hisse senedi piyasası getirilerini ve varlık fiyatlarını tahmin etmenin de temelini oluşturmaktadır. Bu göstergeler aynı zamanda sistematik risk faktörleri olduğundan dolayı bir varlığın veya hisse senedinin fiyatlandırılmasında dikkate alınmalıdır. Çeşitli fiyatlandırma teorileri, farklı sistematik değişkenleri bir faktör olarak tanımlar ve bu faktörü varlık fiyatlarını belirleme amacıyla bir modele dâhil eder. Ekonomik göstergelerinin yanı sıra, politik ortamın da genel olarak ülke ekonomisine ve özelde hisse senedi piyasalarına olan etkisi yadsınamaz. Ekonomik politika belirsizlik (EPU) endeksi bir ülkede hükümetin ekonomi politikalarındaki belirsizliğin ölçülmesinde sıklıkla kullanılmaktadır. Bu tezin amacı; Brezilya, Çin, Hindistan, Rusya ve Güney Kore gibi beş gelişmekte olan ülkede borsa endeksleri, makroekonomik değişkenler ve EPU arasındaki zamana bağlı eşbütünleşme ve nedensellik ilişkisini incelemektir.

Economic growth of a country is highly linked with the changing dynamics of its stock markets. Due to their fundamental roles in economic activities, the operation of stock markets and their up and down movements always carefully followed by financial institutions, corporations, individual investors, and governments. Return of stock markets determined by the systematic effect of macroeconomic indicators. The primary indicators that describe the economy of a country, at the same times, are also the bases for estimating stock market returns and asset prices. These indicators are also systematic risk factors, hence should be considered in the pricing of an asset or a stock. Various pricing theories describe different systematic variables as a factor and incorporate them in a model to determine asset prices. Besides the economic indicators, political climate also has an undeniable effect on the economy in general and on stock markets in particular. Economic Policy Uncertainty (EPU) Index is widely used to measure uncertainties related to government’s economic policies of a country. The aim of the dissertation was to examine the time-varying cointegration and causal relationship between stock market indices, macroeconomic variables and EPU in five emerging countries such as Brazil, China, India, Russia and South Korea. The outcomes of the study have shown mixed results for each country. The outcomes of the Johansen tests indicated the existence of a long-run relationship among the variables in all countries. However, in the short run, the Block Exogeneity Wald Tests have indicated different results for different countries and variables. There was lack of uniformity in the outcome of the causality tests. In the analysis, the study has taken into account the 1990s Asian and Russian crisis as well as the 2008/ 09 Global financial crisis.
Keywords: Causality; Cointegration; Crude Oil; Developed countries; Developing countries; Economic development; Economic indicators; Ekonomik göstergeler; Ekonomik kalkınma; Ekonomik Politika Belirsizliği; Faiz Oranları; Financial management; Finansal yönetim; Gelişmekte olan ülkeler; Ham Petrol Economic Policy Uncertainty; Hisse Senedi Piyasası; Interest Rates; Koentegrasyon; Management; Menkul değerler borsası; Nedensellik; Stock exchanges; Stock Market; Yönetim